Analisis Faktor Yang Mempengaruhi Lama Perawatan Pasien Pasca Operasi Di RSUD Bung Karno Surakarta - Dyah Ayu Pitaloka; Sri Wulandari; Aries Widyoko (MEDIKA TRADA, 2026)
A health service facility is a tool and/or place used to carry out health service efforts, both promotive, preventive, curative and rehabilitative. Hospitals must pay attention to the quality and safety of patients. One of the indicators of the quality of hospital inpatient services is Length of Stay (LOS). This study aims to analyze the factors that affect the Length of Stay (LOS) of postoperative patients at Bung Karno Hospital Surakarta and determine the most dominant factors. The research method used a retrospective quantitative design with patient medical record data for the period January-December 2025 as many as 350 samples determined using the Slovin formula. Data analysis was carried out bivariously using the Chi-square test and the Eta test, as well as multivariate analysis using binary logistic regression. The results of the study showed that most patients experienced non-ideal LOS. Age variables and comorbid diagnosis had a significant association with LOS, while gender, type of surgery, complications, way home, and payment type showed no significant relationship. Multivariate analysis showed that comorbid diagnosis was the most dominant factor influencing LOS, followed by age. The conclusion of this study shows that the length of postoperative patient care is more influenced by clinical conditions, especially comorbid diagnosis and age. Therefore, it is recommended that hospitals improve the management of patients with comorbidities as well as the quality of medical record recording to support clinical decision-making and improve service quality.